A Comparative Study of the Stress Distribution in Different Endodontic Post-Retained Teeth with and without Ferrule Design—A Finite Element Analysis. (7th July 2011) - Garhnayak, Lokanath; Parkash, Hari; Sehgal, D. K.; Jain, Veena; Garhnayak, Mirna
Abstract : Purpose . To analyze the stress distribution in an endodontically treated maxillary central incisor restored with various post-core systems and assess the benefit of ferrule using finite element analysis. Material and Methods . Twelve models with metal ceramic crown were created based on the combination of three types of post-core systems (titanium post-composite resin core, nickel-chromium post-core, and fiber reinforced composite resin post-composite resin core), two varieties of posts (tapered, parallel), and with or without ferrule. 100 N load was applied in three directions and the von Mises stress was compared. Results . Ferrule made no difference in stress distribution for the titanium and nickel-chromium posts, though it showed some stress reduction in fiber-reinforced composite resin posts. Nickel-chromium cast post-core transmitted the least amount of stresses to the dentin despite producing the maximum stress. Conclusion . Incorporation of ferrule offered some degree of stress reduction in nonmetal post, and it increased the stresses within cervical dentin.